Analysis of the Layout of Passive Safety Systems When the Spent Fuel Pool Is Built in the Containment - Zhenjie Gu; Xiaopan Jia; Jincheng Su (Energies)
The Spent Fuel Pool (SFP) is part of the fuel handling and storage system and is generally arranged in an independent building on the Nuclear Island (NI) of Nuclear Power Plants (NPPs). According to the HAF102—Safety Regulations for Nuclear Power Plants Design, it is necessary to ensure the smooth implementation of the safety functions of the SFP under various operating conditions. If the SFP is arranged inside containment, its protection requirements for external events will be significantly reduced, but new requirements will be raised for accident response measures inside containment, namely, that the system performs safety functions to ensure the long-term cooling of both the reactor core and spent fuel components. The reactor type that employs passive principles to realize the above functions requires a reasonable design of the layout of the Passive Safety System (PSS) to ensure nuclear safety. Based on existing reactor schemes, this article analyzes the design of a full-range passive concept for these reactors with an SFP built-in containment. The main focus of this article is on the long-term natural circulation process of PSS in containment under conditions of hypothetical accidents, and the arrangement of system items. Conceptual plans for the operation and layout of the safety system are obtained, which can provide references for the research and design of NPPs with SFP built-in containment.